You can't teach a kid to ride a bike at a seminar : Sandler training's 7-step system for successful selling - Sandler, David H. (McGraw-Hill, 2015)
Providing skills designed for todays highly competitive and more complex sales landscape; this powerful guide will show you how to take the lead in the buyer/seller dance; have a process for answering questions from prospects; move the relationship forward without becoming an unpaid consultant; use online research to turn cold calls into warm calls; and more. --